PENGARUH PENAMBAHAN ETANOL PADA BAHAN BAKAR PERTALITE TERHADAP PERFORMA MESIN EMPAT LANGKAH 150 CC - Rosady, Siti Duratun Nasiqiati; Wafa, Ahmad Khoirul; Sari, Eli Novita (Jurnal Inovasi Teknologi Manufaktur, Energi dan Otomotif, 2023)
Motorcycles are piston-engined vehicles that are widely used in society. Because of the ease of use, lower prices, and more efficient operational costs compared to other means of transportation. The engine produces performance in the form of power and torque which can be increased by increasing the quality of the fuel used as an energy source in the engine. The dependent variable in this study is the power test, torque test and specific fuel consumption test. The aims of this study were (1) to determine the performance and specific fuel consumption produced by motorcycles by mixing pertalite and ethanol fuels. (2) to find out how much the composition of the fuel mixture can produce the best performance. Comparison of 4 variations of fuel types, namely: pure Pertalite (100%), Pertalite 90% + 10% Ethanol, Pertalite 80% + 20% Ethanol, Pertalite 70% + 30% Ethanol. This study used a dynotest with the specifications of the super dyno 50 L-Inertia as a test tool for power, torque and specific fuel consumption. The engine speed is varied from 1000 to 10000 with a range of 1000 between rpm. Based on the results of the research that has been done, it shows the effect of mixing pertalite and ethanol on the performance and specific fuel consumption of a 150 cc four-stroke motorbike. The maximum engine performance is obtained from the fuel mixture (90% Pertalite + 10% Ethanol) with a power of 0.72 kW at 8000 rpm engine speed, the largest torque is 0.75 Nm at 4000 rpm engine speed, and the lowest specific fuel consumption is 2.6178 kg/kW hour at 8000 rpm engine speed.